Empathetic Orientation in Dentistry students from Latin America. Literature review. - Constanza Vera (Universidad de Concepción., 2014)
Empathy, defined as 'the capacity to relate to someone else's perspective or mental state', has a strong impact on the physician-patient relationship and has the potential to improve the quality of health care. The Jefferson Scale of Empathy (JSE) measures empathy in terms of quantity. It was created to assist medical students, physicians, and people related to health care in general and it has been validated into Spanish showing adequate psychometric properties. The concern for empathy in dentistry students is related to the need for training not only technically, but also socially skilled professionals, since social abilities have a strong impact on performance as well as in the patient's appreciation and satisfaction. The goal of this report is to show all the studies using the JSE scale for measuring empathy in dentistry students from Latin America.The reviewed studies show the empathy levels vary in Latin-American dentistry students when comparing gender and class year variables. Also, there is a tendency to find higher empathy levels when it comes to women's performance and that of those soon to be graduate. However, the criteria did not account for more than 20% of the variance of empathy in these studies. Therefore, it would be necessary to keep researching in this field, taking different predictor variables into consideration in order to understand what factors are associated with the presence and intensity of empathy, and their impact in clinical practice.